Measurement of health and social behaviors in schoolchildren: Randomized study comparing paper versus electronic mode - Šmigelskas Kastytis; Lukoševičiūtė Justė; Vaičiūnas Tomas; Mozūraitytė Kristina; Ivanavičiūtė Urtė; Milevičiūtė Ieva; Žemaitaitytė Monika (Sciendo, 2019)
Electronic survey mode has become a more common tool of research than it used to be previously. This is strongly associated with the overall digitization of modern society. However, the evidence on the possible mode effect on study results has been scarce. Therefore, the aim of this study is to investigate the comparability of findings on health and behaviours using a paper-versus-electronic mode of survey with randomization design among schoolchildren.